2008
DOI: 10.1016/j.jinsphys.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Gut pH, redox conditions and oxygen levels in an aquatic caterpillar: Potential effects on the fate of ingested tannins

Abstract: Larvae of the freshwater moth Acentria ephemerella (Pyralidae, Lepidoptera) can fully develop on Myriophyllum spicatum, a submerged macrophyte containing 7-10% of its dry mass as tannins. We investigated the physicochemical gut parameters of larvae fed with M. spicatum or Potamogeton perfoliatus, a food plant lacking tannins, and the chemical fate of ingested polyphenols. Microelectrode studies revealed that larval midguts were slightly alkaline (pH 8) and had a positive redox potential. Whole guts were oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…For example, hydrolyzable tannins are hydrolyzed in vivo in lepidopterans, beetles, and sawflies (Gross et al 2008;Lahtinen et al 2005;Salminen and Lempa 2002). In our study, ellagic acid was found after in vitro incubation of ellagitannin-containing plant extracts (e.g., A. castaneifolia and T. catappa in Figs.…”
Section: The Fates Of Individual Phenolic Compounds In Vitro and In Vivosupporting
confidence: 52%
See 1 more Smart Citation
“…For example, hydrolyzable tannins are hydrolyzed in vivo in lepidopterans, beetles, and sawflies (Gross et al 2008;Lahtinen et al 2005;Salminen and Lempa 2002). In our study, ellagic acid was found after in vitro incubation of ellagitannin-containing plant extracts (e.g., A. castaneifolia and T. catappa in Figs.…”
Section: The Fates Of Individual Phenolic Compounds In Vitro and In Vivosupporting
confidence: 52%
“…These data demonstrate that geraniin is modified by exposure to high pH either in vivo or in vitro, possibly by oxidation. It previously has been proposed that ellagitannins (Barbehenn et al 2008;Gross et al 2008) and galloyl glucoses (Salminen and Lempa 2002) are oxidized in the guts of lepidopteran Table 1. For abbreviations and the MS and UV spectral data of compounds, see Tables 4 and 5 larvae, leading to oxidative stress to the larvae (Barbehenn et al 2006a(Barbehenn et al , 2008.…”
Section: The Fates Of Individual Phenolic Compounds In Vitro and In Vivomentioning
confidence: 99%
“…The insect gut as a bacterial habitat shows different morphologies, generally depending on the insect order (45); furthermore, the gut morphology is sharply changed by metamorphosis, according to the life cycle of the insect (46). Additionally, the oxygen availability can be influenced by gut shape (47), metabolism of colonizing bacteria (48,49), and partial pressure of oxygen from the outside environment (50), and the pH, from acidic to extremely alkaline conditions, is determined by different gut compartments in diverse insect individuals (51,52). These diverse gut conditions may cause the variation in host-specific gut microbiota in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Like some terrestrial Lepidoptera larvae, aquatic caterpillars may ignore quantitative plant defences, which affect nutrient uptake in the gut, as they tolerate them better. For example, Acentria ephemerella, a close relative of P. stratiotata, tolerates tannins, which are degraded in its gut in a similar manner as the terrestrial caterpillar Lymantria dispar (Gross et al, 2008). But, they grow faster on a plant low in tannins (Potamogeton perfoliatus) than on a plant high in tannins (M. spicatum) (Choi et al, 2002).…”
Section: Discussionmentioning
confidence: 99%